Identifikasi Faktor–Faktor yang Berpengaruh Terhadap Medical Tourism pada Rumah Sakit di Indonesia - Kusumawati, Ayu Nadya (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2018)
Medical tourism is an activity carried out by an individual to get a health service or medical care abroad. In the effort to develop the health system and competition and the impact of health globalization, it does not rule out the possibility that medical tourism raises intense competition among hospitals in providing quality services and superior service products provided by hospitals in attracting foreign patients to come get treatment. Objective of this research is to determined factors that affect hospital to be medical tourism’s aim. Methods in this research is literature review from international journals. The results is hospital needs to improve their physician’s skill, facilities, accessibility, and promotions. So that medical tourism is a new phenomenon for hospitals in Indonesia to prepare professional and superior health personnel and sophisticated health technology as a developmental need for medical tourism. Need to study or identify factors that influence medical tourism in hospitals in Indonesia.